GARDU RONDA SEBAGAI KARYAARSITEKTUR VERNAKULAR KAJIAN TERHADAPBENTUK, STRUKTUR DAN FUNGSI - Sumarjo H., Sumarjo (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This research is aimed to identify the typology of form, structure and function of the Watchman Station Patrol building as masterpiece of architecture vernacular. Sample of research amount of 10 buildings of watchman station, taken by snowball in region Sleman and its surroundings. To analyze the variation of form growth, structure and function of the Watchman station Patrol building, a fundamental approach model of typology and also continuity and change is applied. Result of research indicates that geometry of space of the Watchman Station Patrol building showing the remain uniform, that is the square geometry. Typology of structure of the Watchman Station Patrol building shows the conventional uniform; that is; system structure mark with lines with the wall at one blow as burden taker, open wall is mostly arranged in watchman station, especially at shares fagade. Watchman station also Shows a manifest Function for rendezvous as well as keep the warehouse places. Locus of watchman station determined by road axis of the orchard collector and center of the local countryside governance. The latent function could be changed overtime depend on the society need; it supports the social and economic function of society. However, the core elements are remain, those are geometry of space, super structure and setting of locus of the Watchman station Patrol building. Keywords: vernacular, form, structure, function